Developing a food basket for fulfilling physical and non-physical needs in Cyprus. Is it affordable? - Chrysostomou, Stavri; Andreou, Sofia N.; Polycarpou, Alexandros (My University, 2017)
Background: An acceptable and affordable food basket (FB) is necessary to meet not only physical (healthy) needs but also the non-physical needs of individuals and communities. Methods: FBs were developed based on the Cypriot national food-based dietary guidelines for six types of household: single woman (±40 years), single man (±40 years), a couple (±40 years) without children, single woman (±40 years) with two children (10-year-old boy and 14-year-old girl), single man (±40 years) with two children and a couple (±40 years) with two children. Non-physical needs (kitchen equipment, physical activity and other related functions of food) were added to the baskets. The cost, acceptability and feasibility of FB were examined through the focus group discussions. Affordability was defined as the cost of the each basket as a percentage of household income (Guaranteed Minimum Income [GMI]). Results: The budget for healthy food has the highest proportion in the total food budget (83-89%) compared with the other components. The part of the budget required for other functions of food is small compared with that of healthy food and ranged between 4.7 and 6.7% of the total monthly budget. For low-income families, the proportion of income that needs to be spent on the FB for physical needs and FB for physical and non-physical needs ranged from around 39 to 72% and 47 to 81%, respectively. Conclusions: The FB fulfilling physical and non-physical needs is not affordable among the low-income families (mainly with children) receiving the GMI scheme in Cyprus.
Keywords: Budgets; Child; Cyprus; Food; Income